2016
DOI: 10.1016/j.dcn.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Mu desynchronization during observation and execution of facial expressions in 30-month-old children

Abstract: Simulation theories propose that observing another’s facial expression activates sensorimotor representations involved in the execution of that expression, facilitating recognition processes. The mirror neuron system (MNS) is a potential mechanism underlying simulation of facial expressions, with like neural processes activated both during observation and performance. Research with monkeys and adult humans supports this proposal, but so far there have been no investigations of facial MNS activity early in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 84 publications
9
41
2
Order By: Relevance
“…Yet, mu suppression is reported to be modulated by contextual information, such as the actor's familiarity (Oberman et al, 2008) or their reward value (Gros et al, 2015), or gaming context in which the hand gestures are viewed (Perry et al, 2011). In addition, viewing facial gestures that do not suggest object interaction or deliberate action also seems to modulate mu rhythm (Moore & Franz, 2017;Moore et al, 2012;Rayson et al, 2016;Rayson et al, 2017). Thus, explanations which restrict mu suppression to voluntary or object-related actions are unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, mu suppression is reported to be modulated by contextual information, such as the actor's familiarity (Oberman et al, 2008) or their reward value (Gros et al, 2015), or gaming context in which the hand gestures are viewed (Perry et al, 2011). In addition, viewing facial gestures that do not suggest object interaction or deliberate action also seems to modulate mu rhythm (Moore & Franz, 2017;Moore et al, 2012;Rayson et al, 2016;Rayson et al, 2017). Thus, explanations which restrict mu suppression to voluntary or object-related actions are unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…The ADFES is freely available for research from the Psychology Research Unit at the University of Amsterdam. Neutral faces were recorded by OK. Past research has validated mouth opening videos of actors as non-emotional (Rayson et al, 2016). Videos used in the present study were made similar to Rayson et al's (2016) and the ADFES stimuli in terms of duration, brightness, size, and contrast.…”
Section: Stimuli and Designmentioning
confidence: 96%
See 1 more Smart Citation
“…Recent contributions to our understanding of emotion simulation have come from work exploring mu modulation during observation of different types of facial expressions. In a study in infants, Rayson et al (2016) found significant bilateral mu suppression for nonemotional expressions (mouth opening), but only right-hemispheric suppression for emotional (happy or sad) facial expressions. An emotion categorisation study from our group reported greater mu suppression while viewing dynamic videos of non-emotional facial movement (mouth opening) compared to non-biological movement (kaleidoscope pattern), but this was not observed for emotional faces (happy or sad) (Karakale et al, 2019).…”
Section: Introductionmentioning
confidence: 90%
“…EEG objectively and non-invasively quantifies electrical cerebral activity timelocked to stimulus presentation. Emotional facial expressions are often used as stimuli to study socially complex skills, including empathy, as facial expressions powerfully communicate emotions to others in everyday life (Moore, Gorodnitsky, & Pineda, 2012;Rayson, Bonaiuto, Ferrari, & Murray, 2016). EEG were shown useful in demonstrating that the mere observation of emotional facial expressions elicits similar brain activation patterns than those involved in their expression (Rayson, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%